To solve the expression \((\frac{5}{6})^{10} \div (\frac{5}{6})^{3}\), we can apply the Quotient Rule of Exponents. The Quotient Rule states that when you divide two exponential expressions with the same base, you subtract the exponents:
\[ a^m \div a^n = a^{m-n} \]
In this case, \(m = 10\) and \(n = 3\). Thus, we have:
\[ (\frac{5}{6})^{10} \div (\frac{5}{6})^{3} = (\frac{5}{6})^{10-3} \]
Calculating \(10 - 3\) gives us \(7\). Therefore, the expression simplifies to:
\[ (\frac{5}{6})^{7} \]
The exponent in this equivalent form is \(\boxed{7}\).